Assessment and Prediction of Hydrometeorological Drought in Corong River Basin, Indonesia - Affandy*, Nur Azizah; Iranata, Data; Anwar, Nadjadji; Maulana, Mahendra Andiek; Prastyo, Dedy Dwi; Yusop, Zulkifli; Wardoyo, Wasis (Graduate School of Universitas Syiah Kuala, 2023)
Hydrological drought analysis in a river basin is crucial because it impacts water resource management, agriculture, drinking water supply, industry, ecology, and disaster risk mitigation. It plays a key role in water usage planning, safeguarding agricultural yields, and ensuring a stable drinking water supply. In the context of this research, the Corong River basin is used as a case study. This study aims to determine the level of hydrological drought (deficit) using the Threshold Level Method (TLM) and predict hydrological drought using the Seasonal Autoregressive Integrated Moving Average (SARIMA) model. This model understands the characteristics of drought and predicts drought in the Corong River basin for early mitigation and anticipation of drought in the region. The results of this research indicate a strong relationship between the Hydrological Drought Index (HDI) and streamflow and Precipitation (PRCP), which can be used to forecast future droughts. This model is highly robust and accurate in observing the level of hydrological drought (deficit, duration, and sharpness) and predicting drought events in the Corong River basin. These findings have significant practical implications for water management and disaster risk mitigation in this river basin while also advancing the scientific understanding of hydrological drought.